ANALISIS BANDWIDTH JARINGAN INTERNET PUSAT LAYANAN INTERNET KECAMATAN (PLIK) DENGAN METODE FUZZY SUGENO DI PROVINSI BANTEN - Mochamad Natsir (Universitas Serang Raya, 2016)
Internet is a major part in the development and progress of the nation, especially the Indonesian nation, government issued a policy in Candy Kominfo about PLIK program (District Internet Service Center) which has a strategic role in sustaining and supporting economic activity, strengthening defense and security and the intellectual life of the nation. In the implementation of the program PLIK (District Internet Service Center) have not been targeted in a side benefit, this program should have as a means to meet the needs of information and knowledge, but rather the mere entertainment and more oriented to the business, which is equated with the cafe. This study attempts to retrieve the data in bandwidth usage that will be processed by the method of Fuzzy Sugeno and will generate average maximum bandwidth usage in applications Browsing, Download and Streaming. In determining the average bandwidth usage using Fuzzy Sugeno, From the average bandwidth will be used as a reference in determining the usage restrictions Browsing, Download and Stream with the aim to give control over bandwidth usage for applications Browsing, Download and Streaming.